(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Mangrove is one of coastal ecosystem which has a major role to sequastrate and store carbon. Mangrove stand structure delivers a significant contribution for estimating biomass carbon stock through individual scale allometric equations. On the other hand, the aboveground carbon research on the community scale was conducted in Teluk Benoa. The study aimed to establish a model for estimating mangrove aboveground carbon stock from the multiple variables of mangrove stand structure. A stratified purposive sampling method was applied for distributing quadratic samples. Three mangrove zones (1–3) were identified using mRE-SR (modified red edge-simple ratio) interpretation based on mangrove species domination. A common allometric equation was applied for estimating aboveground carbon stock. The result showed that mangrove stand structure in zone 1 was significantly different to other zones. Aboveground carbon stock was 193.45±34.88 tons C/ha on entire sites. It was found highest in zone 1 which was dominated by Sonneratia alba. The linear regression and Akaike’s Information Criterion (AIC) analysis showed that the combination of canopy cover, tree density, sapling density and tree diameter became the best model in estimating carbon stock at the community scale. The multiple model had the highest regression coefficient and the lowest root mean square error (RMSE) value. We expect that the multiple variable model could be more efficient and accurate to estimate aboveground carbon stock on community scale.